(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
This study presents a research project aiming at capturing and describing internal diversity and multi-variant nature of contemporary German in the light of demands of teaching German as a foreign language at universities in language degrees (German studies, applied linguistics, languages in business), where German is the first or second leading foreign language. The paper outlines the specific research questions and aims, the state of research in this area so far, the research design together with the associated research risks, and the research methods. The research project is situated at the intersection of the teaching of German as a foreign language and Germanic linguistics